Changes in Endogenous Cytokinins and in vitro Photoperiodic Flowering Induction in Cichorium intybus L. - Attibayeba; Badila, Jean-Luc; Marie Genevieve, Okiemy-Akeli (Pakistan Journal of Nutrition, 2010)
Cytokinins were extracted from the explants of Cichorium intybus L. roots grown under flowering inductive (long-day and red light), or non inductive conditions (short-day). Flowering was expressed as percent after 8 weeks of their development. Overall, cytokinins levels exhibited biphasic trends with initial increasing concentrations followed by a decrease over time. The highest content of cytokinins was observed in explants exposed to either red light or long-day periods. Measured maximum levels of up to 525 ng.g-1 dry weight were obtained under red light exposure conditions. Cytokinins concentrations measured in materials cultured under long-day conditions were slightly lower by quite similar to those obtained under red-light growth conditions. In contrast, much lower peak values (not exceeding 155 ng.g-1 dry weight) were obtained under short-day experimental conditions. The in vitro development of C. intybus under both long-day periods and exposure to red light resulted in percent flowering of 55.75% and 64.28%, respectively. No flowering was observed under short-day experimental conditions. Overall, our results show that both endogenous content of cytokinins and flowering of C. intybus grown in vitro are dependent on both light quality and length of the photoperiod.